Diversity of Crustaceans Family: Portunidae in East Coast Mangrove Forest Reserve Mendahara Resort Tanjung Jabung Timur - Wafiq Nadya; Mahya Ihsan; Tia Wulandari (Universitas Muhammadiyah Surakarta, 2024)
Crustacea, the largest subphylum in the Phylum Arthropoda, inhabits fresh and seawater. Their bodies are divided into three segments namely cephalo, thorax, and abdominal, or cephalothorax in some crustacean species and they breathe through gills. Crabs are one of the biota that can function as aquatic bioindicators in addition to making a major contribution to nutrient recycling. In the muddy parts of the mangrove forest, the decapod crustacean species Portunidae plays an important ecological function in the environment. This research aims to categorize the crustaceans of the Portunidae family in the East Coast Mangrove Forest Nature Reserve and calculate their dominance, uniformity, and diversity indices. The diversity, uniformity, and dominance index of the Crustacean Family Portunidae in the East Coast Mangrove Forest Reserve area was calculated in this quantitative descriptive research. Purposive sampling is a sampling approach used in survey methods used for sample collection. The results showed that the two different types of crustaceans collected for this study were Thalamita crenata (4125 individuals) and Scylla olivacea (a total 19 individuals). This research shows that in the East Coast Mangrove Forest Reserve area, Thalamita crenata is the most commonly found crustacean species in the Portunidae family. The overall dominance index is in the medium group, while the overall diversity and uniformity index is in the low group. The results of Principal Component Analysis (PCA) show that the environmental factor with the closest relationship and positive correlation between species diversity and uniformity and environmental parameters is salinity.